Financial Performance Affecting Company Compliance in Membership of BPJS Ketenagakerjaan - Reza Maulana Saragih; Sri Mulatsih; Bambang Juanda (International Journal of Social Science and Business, 2023)
The issue with compliance is a barrier since it unquestionably prohibits BPJS Ketenagakerjaan from offering the optimum protection to all Indonesian workers. The Covid-19 pandemic's state is a contributing factor in the low compliance of BPJS Ketenagakerjaan participation, which affects the state of the business's financial performance. Many businesses or memberships become non-compliant as a result, such as paying their required dues late or not at all. Based on this context, the research's three main goals are to: (1) ascertain the evolution of BPJS Ketenagakerjaan membership in 2019–2020; (2) ascertain the impact of the company's financial performance on membership compliance; and (3) ascertain improvement methods. The two methodologies used in this study are quantitative and qualitative methods. The first strategy uses logistic regression and quantitative descriptive techniques. The second strategy is a qualitative one that makes use of focus group discussions (FGD). The type of data used is primary data collected using the Focus Group Discussion (FGD) model and secondary data using the company's annual report from the Indonesia Stock Exchange (IDX) from 2019-2020. Return on Assets (ROA), Return on Equity (ROE), and Debt to Assets Ratio (DAR) factors all affect BPJS Ketenagakerjaan membership compliance, making them four independent variables in financial performance. Compliance is unaffected by another financial performance metric called the Debt to Equity Ratio (DER). The FGD technique, which removes dues sanctions that burden membership during the pandemic, increases socializing and education on a regular basis in order to increase compliance.